A rapid nucleic acid concentration measurement system with large field of view for a droplet digital PCR microfluidic chip. Issue 19 (11th August 2021) - Shen, Jinrong; Zheng, Jihong; Li, Zhenqing; Liu, Yourong; Jing, Fengxiang; Wan, Xinjun; Yamaguchi, Yoshinori; Zhuang, Songlin
Abstract : Droplet digital polymerase chain reaction (ddPCR) is an effective technique, with unparalleled sensitivity, for the absolute quantification of target nucleic acids. Abstract : Droplet digital polymerase chain reaction (ddPCR) is an effective technique, with unparalleled sensitivity, for the absolute quantification of target nucleic acids. However, current commercial ddPCR devices for detecting the gene chip are time consuming due to complex image stitching. To address this issue, we propose a universal concentration determination system and realize one-time gene chip imaging with high resolution. All the functional units are controlled by self-developed software using the PyQt5 module in Python. Without stitching technology, images of the ddPCR chip (28 mm × 18 mm) containing 20 000 independent 0.81 nL micro chambers can be obtained in less than 15 seconds, which saves about 165 seconds. A white laser light source (2 mW cm −2 ) was employed as a substitute for the mercury lamp. Its wavelength matches well with typical fluorescent dyes ( e.g., HEX, ROX and Cy5), and thus it can strengthen the fluorescence intensity for weak signals. The results also demonstrated that the correlation coefficient for the measured concentration and theoretical value was above 99%, by testing the ddPCR products with COVID-19 virus. Such a system can greatly reduce the time required for image acquisition and DNA concentration determination, and thus is able to speed up the lab-to-application process for ddPCR technology.